2021
DOI: 10.3389/fpsyt.2021.635514
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Personal Recovery of People With Complex Mental Health Needs: The Development of a Psychosocial Intervention Through User-Centered Design

Abstract: Long-term admissions in psychiatric facilities often result in a gradual erosion of the identity of people diagnosed with severe mental illnesses (SMIs) into merely “patient.” Moreover, experiences of loss often reduced people's sense of purpose. Although regaining a multidimensional identity and a sense of purpose are essential for personal recovery, few interventions specifically address this, while at the same time take people's often considerable cognitive and communicative disabilities into consideration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 80 publications
0
27
0
Order By: Relevance
“…The iterative stages in the research process are shown in Figure 1 . The participation of MHNs throughout the design process has several purposes: (a) at the start, the participation of MHNs helped us to explore the context of mental health professionals, including their worldviews and needs; (b) the MHNs could participate in constructing and/or utilizing prototypes; (c) the MHNs could give feedback in user tests; and (d) the MHNs could give insight into the system in which an intervention should be implemented and the needs of MHNs in caring for patients with a psychotic disorder [ 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The iterative stages in the research process are shown in Figure 1 . The participation of MHNs throughout the design process has several purposes: (a) at the start, the participation of MHNs helped us to explore the context of mental health professionals, including their worldviews and needs; (b) the MHNs could participate in constructing and/or utilizing prototypes; (c) the MHNs could give feedback in user tests; and (d) the MHNs could give insight into the system in which an intervention should be implemented and the needs of MHNs in caring for patients with a psychotic disorder [ 29 , 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The actual implementation of recovery-oriented care approaches in practice, however, remains challenging ( 13 , 33 ), particularly for mental health care systems in transition ( 23 , 24 , 35 ). Furthermore, when care and treatment is primarily focused on lengthy inpatient care ( 27 , 36 ), it can lead to challenges in maintaining a sense of purpose, which can make formulation of recovery goals challenging ( 37 ) and can affect self-identity ( 37 ). Designing and implementing holistic mental health care and support implies not only adopting approaches that facilitate individual goal setting and planning of treatment, but also delivering care within the service user's personal and social context, where recovery goals related to restoration of social identity and roles can potentially be formulated and realized.…”
Section: Introductionmentioning
confidence: 99%
“…Clients with an IQ between 70 and 85 constitute a substantial part of the client population in secure facilities. In addition, they are internationally recognised to share characteristics and needs with clients with mild intellectual disability, as a result of which clients with borderline intellectual functioning are often grouped together with clients with mild intellectual disability (see e.g., Berger et al, 2023; Sauter et al, 2023; Smit et al, 2023; Van Cappellen et al, 2023). Therefore, we grouped participants with both intellectual levels into a single sample.…”
Section: Methodsmentioning
confidence: 99%